Une réponse à Gabriel Josipovici et à son The Book of God : Pour une approche renouvelée des études comparatistes sur la Bible et la littérature - Alexandra Ivanovitch (Revue LISA)
In order to study the Bible, one needs to read Ulysses, and if one wants to assess so-called imaginative literature, one has to read the Gospels: in The Book of God, Gabriel Josipovici invites us to reunite exegesis and literary criticism. Not only does he study the “Bible as literature”, and question the validity of certain categories pertaining to textual criticism, but, also, he does not hesitate to comment on literature through a Biblical prism, by invoking works from theologians and exegetes who sometimes embark on literary criticism without quite knowing it. The critic also reflects on the status of the apocrypha, on the margins of the Biblical canon, which lie between the Bible and literature, between the sacred and the profane. And all the rest is literature… To read Josipovici’s The Book of God seems unavoidable in order to reflect on the development of the comparative studies dealing with the relationship between the Bible and literature. By the subtitle the author chose for his book, following “reader-response criticism”, Josipovici wanted to “respond to the Bible.” Let us continue this unending chain of questions and answers, and respond to his book by this article.